2017
DOI: 10.3892/mmr.2017.7828
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-137 has a suppressive role in liver cancer via targeting EZH2

Abstract: A variety of microRNAs (miRs) have been demonstrated to be associated with the development and malignant progression of human cancer; however, the regulatory mechanism of miR-137 underlying hepatocellular carcinoma (HCC) growth and metastasis still remains to be fully revealed. In the present study, reverse transcription-quantitative polymerase chain reaction and western blot were used to examine mRNA and protein expression. MTT assay, wound healing assay and Transwell assay were performed to determine cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…36 Cui et al have found that miR-137 inhibited HCC growth and metastasis by suppressing the expression of EZH2. 38 Here, bioinformatics analysis and dual luciferase reporter assay showed that EZH2 was a target gene of miR-214-3p, and we identified the functional role of miR214-3p/EZH2 axis in HCC cells.…”
Section: Discussionmentioning
confidence: 87%
“…36 Cui et al have found that miR-137 inhibited HCC growth and metastasis by suppressing the expression of EZH2. 38 Here, bioinformatics analysis and dual luciferase reporter assay showed that EZH2 was a target gene of miR-214-3p, and we identified the functional role of miR214-3p/EZH2 axis in HCC cells.…”
Section: Discussionmentioning
confidence: 87%
“…High expression of miR-92a 25 , miR-221 40 , miR-487a 45 and miR-1468 51 might indicate poor prognosis in HCC. Low expression of miR-33a 63 , miR-122 72 , miR-137 76 , miR-194 90 and miR-940 142 in HCC patients were observed to have unfavorable prognosis. High levels of miR-7/21/107 and low expression of maspin implied poor survival of HBV-related HCC 56 .…”
Section: Acting As Diagnostic and Prediction Markers In Hccmentioning
confidence: 94%
“…Low expression of miR-296 in HCC patients might have large tumor size and advanced TNM stage 108 . Low expression of miR‑137 was significantly closely related with lymph node metastasis, vein invasion and advanced clinical stage in HCC 76 .…”
Section: Acting As Diagnostic and Prediction Markers In Hccmentioning
confidence: 95%
See 2 more Smart Citations